DATA VISUALIZATION AS ARTISTIC EXPRESSION - Sharma, Nittin; Sarkar, Sudeshna; Khan, Akhilesh Kumar; Bhargava, Shilpa; Karthik K; Kumar, Prince; Pawar, Amrut Ramchandra (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The data visualization has not only become a more communicative, rather than an aesthetic practice, but also rather an artistic one, where datasets can cease to be the input of information, but a resource of expression that might elicit an emotional reaction, a story, and a cultural background. The paper will consider data visualization as an art form by following the history and theoretical context of data visualization beginning with the early scientific diagrams and the art of cartography to the Bauhaus inspired minimalism and the emergence of computational data art. Under this outlook, data becomes something manipulable, decontextualized, or repackaged so as to generate metaphor, critique systems or provoke sensory engagement. The aesthetics such as theory of color, psychology of perception, composition and generative form-making are discussed and how artists use geometric, organic and algorithmic formations to make readings, which are not so abstract that they cannot be interpreted, look appealing to the eye. The current processes are shifting towards creative code, interchangeable systems and generative models run on AI in order to offer a hybrid form of artistic practice that integrates both the customary practice and the sophisticated computational approaches. The paper will be based on the exploration of how cross-disciplinary collaborations between artists, scientists and technologists can enhance the expressive potential of data through the study of landmark data-art projects in museums, galleries and in-the-street installations. Along these processes, the paper outlines key concerns that are associated with data ethics, representational imprecision, scalability challenges, and the viability of digital artworks with the passage of time.